Analysis of the Word Nadhir in the Qur'an - Rahma Azizi Meliasani; Wahyu Nur Sinta Sari; Sekar Galuh Putri Wiseno; Nadia Alisyia Nuri (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
This study addresses a research gap in the linguistic and semantic analysis of the word